2009
DOI: 10.3747/co.v16i0.409
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Management of Small Renal Masses

Abstract: Peak rcc incidence occurs in patients more than 65 years of age 4 . Patients in that age group often have significant medical comorbidities that might affect the choice of therapeutic options.Management of srms must be individualized, because several patient-and tumour-related factors affect management strategy. The identification of these parameters necessitates revisiting the natural history of srms and the safety and efficacy of the various available treatment modalities. NATURAL HISTORY OF SRMsUnderstandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The European Association of Urology Guidelines on Renal Cell Carcinoma indicate that elderly and comorbid patients with incidentally detected small renal masses can be managed by active surveillance (AS) ( 23 ). However, considering that sporadic RCC has a high risk of metastasis, AS of sporadic RCC should be adopted in patients who cannot tolerate surgery ( 24 ). A population-based study using the Surveillance, Epidemiology, and End Results (SEER)-9 database showed that local treatment modalities utilized with SPRCC were partial nephrectomy in 16% of patients, radical nephrectomy in 33% of patients, and ablation in 5.5% of patients, with no local treatment in 18% of patients ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The European Association of Urology Guidelines on Renal Cell Carcinoma indicate that elderly and comorbid patients with incidentally detected small renal masses can be managed by active surveillance (AS) ( 23 ). However, considering that sporadic RCC has a high risk of metastasis, AS of sporadic RCC should be adopted in patients who cannot tolerate surgery ( 24 ). A population-based study using the Surveillance, Epidemiology, and End Results (SEER)-9 database showed that local treatment modalities utilized with SPRCC were partial nephrectomy in 16% of patients, radical nephrectomy in 33% of patients, and ablation in 5.5% of patients, with no local treatment in 18% of patients ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The European Association of Urology Guidelines on RCC indicates that elderly and comorbid patients with incidentally detected small renal masses can be managed by active surveillance (AS) [ 11 ]. However, considering that the sporadic RCC has a high risk of metastasis, AS of sporadic RCC should only be adopted in patients who cannot tolerate surgery [ 20 ]. A population-based study using the Surveillance, Epidemiology, and End Results (SEER)-9 database showed that local treatment modalities utilized with 2nd RCC were partial nephrectomy in 16% of patients, radical nephrectomy in 33% of patients, and ablation in 5.5% of patients, while 18% of patients received no local treatment [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of laparoscopy and robot assisted technology, nephron sparing partial nephrectomy has become the preferred treatment for early small renal cell carcinoma [ 1 , 12 ]. Tumor itself and patient specific variables can increase the complexity of partial nephrectomy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%